Mythopoesis as a legitimation strategy in discourse - ELHARRAKI, Badia (Revue Internationale du Chercheur, 2022)
This article investigated how media constructs propositions about women subjected to violence in Morocco from a discourse vantage point. It confirmed the view posited in the literature that discourses cannot be understood without taking into consideration the social practices in which they are manifested and take shape. An analysis of the semantic macrostructures (the identified range of cognitive scripts) related to the challenges of women subject to marital violence provides invaluable insights about how these women seek to legitimize their position in the power network by having recourse to one of the four legitimation tactics introduced by Van Leeuwen (2007), namely mythopoesis in order to sensitize the Moroccan society about the threats they faced. The explicit exploration of the narrative is an effective device in locating the way in which they established cognitive scripts related to the imperative to take action to ensure that a change has to be created. Building on the analysis of narrative macrostructures, the study drew on legitimation theory (Van Leeuwen, 2007; Van Leeuwen & Wodak, 1999) to trace the way in which these women seek for legitimation to get their message across that they are were at-risk and vulnerable. Conversely, the violent husbands were constructed as strong, authoritative and cruel. The data used were extracted from a Moroccan talk show “Qesset Nnass” (the story of people) on the Moroccan station Medi 1 TV.